Risk factors for distal junctional kyphosis after posterior spinal surgery in adolescent idiopathic scoliosis: a meta-analysis - Jia, Ruili; Long, Yubin (Frontiers in Surgery, 2023)
Introduction Distal junctional kyphosis (DJK) is a serious complication after posterior spinal surgery in managing adolescent idiopathic scoliosis (AIS). Our study aims to investigate the predictors of DJK in AIS patients. Methods We searched the English databases of PubMed, Embase, and the Cochrane Library for clinical research studies on AIS. To identify the risk factors for DJK, we collected demographic data, such as age, gender, and body mass index (BMI), and sagittal parameters, including preoperative pelvic tilt (PT), sagittal vertical axis (SVA), lumbar lordosis (LL), thoracic kyphosis (TK), thoracolumbar kyphosis (TLK), distal junctional angle (DJA), lowest instrumented vertebrae (LIV) relative to sagittal stable vertebrae (SSV), and postoperative DJA. Data were analyzed by RevMan (5.3 version) and STATA (12.0 version). Results Finally, six included articles (1,240 patients) showed 9% (98 of 1,240 patients) of patients suffering from DJK. Our findings indicated that preoperative TK [p = 0.007, OR = 0.35, 95% CI (0.10, 0.61)], TLK [p < 0.0001, OR = 5.99, 95% CI (3.33, 8.65)], and postoperative DJA [p = 0.002, OR = 0.56, 95% CI (0.21, 0.91)] in the DJK group were markedly higher than those in the non-DJK group. Moreover, patients with LIV above SSV [p < 0.0001, OR = 7.95, 95% CI (4.16, 15.22)] were more likely to develop DJK. No discernible difference was found in age, sex, BMI, preoperative PT, SVA, LL, or DJA between the two groups. Conclusions Regarding the AIS patients, factors such as higher preoperative TK and TLK, higher postoperative DJA, and LIV above the SSV were related to an increased rate of DJK.